ENHANCING GEOGRAPHIC INFORMATION SYSTEMS WITH SPATIAL DATA MINING (Balkan Journal of Applied Mathematics and Informatics, 2025)
This paper explores how Geographic Information Systems (GIS) can be combined with Spatial Data Mining (SDM) to improve the understanding and utilization of large volumes of spatial data. The study begins by defining spatial data and highlighting its significance. It then examines the fundamental concepts of GIS and the methods for managing, analyzing, and modeling spatial data. Furthermore, the research identifies and explains the challenges that arise when integrating GIS with SDM, proposing possible solutions to overcome these issues. This paper provides a detailed insight into the synergy between GIS and SDM tools, aiming to enhance the management and analysis of large spatial data collections.
Keywords: Geographic Information System, Spatial Data Mining, big data.